2017
DOI: 10.1183/13993003.01327-2016
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of insomnia and incident asthma in adults: the HUNT study

Abstract: Insomnia is highly prevalent among asthmatics; however, few studies have investigated insomnia symptoms and asthma development. We aimed to investigate the association between insomnia and the risk of incident asthma in a population-based cohort.Among 17 927 participants free from asthma at baseline we calculated odds ratios and 95% confidence intervals for the risk of incident asthma among those with insomnia compared to those without. Participants reported sleep initiation problems, sleep maintenance problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…Similarly, another study found higher gene expression of Arntl2 (a paralog of Bmal1) and lower of Per2 in severe asthmatics when compared to mild asthmatics and healthy donors (Fajt et al 2015). This suggests a relationship These findings are supported by a recent longitudinal study that demonstrated the association of insomnia and risk of developing asthma in approximately 18,000 participants (Brumpton et al 2017).…”
Section: Asthmasupporting
confidence: 76%
“…Similarly, another study found higher gene expression of Arntl2 (a paralog of Bmal1) and lower of Per2 in severe asthmatics when compared to mild asthmatics and healthy donors (Fajt et al 2015). This suggests a relationship These findings are supported by a recent longitudinal study that demonstrated the association of insomnia and risk of developing asthma in approximately 18,000 participants (Brumpton et al 2017).…”
Section: Asthmasupporting
confidence: 76%
“…Sivertsen et al 20 reported that insomnia was a significant risk factor for incidence of asthma in an 11-year large population-based prospective cohort study consisted of 24 715 participants (OR=1.47; 95% CI 1.16 to 1.86). Brumpton et al 27 also found that insomnia symptoms were associated with increased risk of incident asthma in the same population-based which consisted of 17 927 participants (three insomnia symptoms, OR=1.70; 95% CI 1.37 to 2.11). However, they used questionnaires to define insomnia and provided no information about the severity or duration of their participants’ poor sleep.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, designed studies have shown that asthma control is worse among patients with insomnia . It has even been proposed that insomnia symptoms may precede an asthma diagnosis and that insomnia is a risk factor for asthma . Hence, an alternative implication is that treatment of insomnia may improve asthma control.…”
Section: Discussionmentioning
confidence: 99%